ANSWERING EXAMINATION QUESTIONS. - Maxwell, Arthur D. (The Accounting Review, 1956)
This article provides tips for answering examination questions of certified public accountants' (C.P.A.) examination. The results of C.P.A. examinations given in the past show that each year the percentage of candidates passing the entire examination is relatively low, ranging from ten to thirty-five per cent in the various states. Examiners have long been puzzled by this condition. Is it due to insufficient formal education, lack of practical experience, inability to express oneself or other causes. While it was found that the best of candidates, under the pressure of the examination, will give an occasional poor answer.